Microstructural Characteristics and Mechanical Properties of Friction Stir Spot Welded 2A12-T4 Aluminum Alloy - Huijie Liu; Yunqiang Zhao; Xingye Su; Lilong Yu; Juncai Hou (Advances in Materials Science and Engineering)
2A12-T4 aluminum alloy was friction stir spot welded, and the microstructural characteristics and mechanical properties of the joints were investigated. A softened microstructural region existed in the joint, and it consisted of stir zone (SZ), thermal mechanically affected zone (TMAZ), and heat affected zone (HAZ). The minimum hardness was located in TMAZ, and the average hardness value in SZ can be improved by appropriately increasing welding heat input. The area of complete bonding region at the interface increased with increasing welding heat input because more interface metals were mixed. In a certain range of FSSW parameters, the tensile shear failure load of the joint increased with increasing rotation speed, but it decreased with increasing plunge rate or decreasing shoulder plunging depth. Two kinds of failure modes, that is, shear fracture mode and tensile-shear mixed fracture mode, can be observed in the tensile shear tests, and the joint that failed in the tensile-shear mixed fracture mode possessed a high carrying capability.